Pre-Experimental Study to Assess the Impact of The teaching Program on Knowledge and Attitude regarding Disaster Management among the Nursing Students of Selected Nursing Colleges of Himachal Pradesh - Thakur, Nitika; Solomon, Smriti G. (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: The aim of this pre-experimental study is to examine how the teaching program affects disaster management knowledge and attitude in Himachal Pradesh nursing students. Method: Pre-experimental design with one group pre-and post-test was used in this study. The researcher used quantitative approach. About 450 samples were taken for the investigation. Simple random sampling was utilized because the sample was available and met inclusion requirements. Data were presented using descriptive and inferential statistics. The knowledge and attitude of the pre- and post-test scores were compared using the t-test. Chi-square tests determined the connection between knowledge and attitude and demographic variables. Result: Results say that pre-test, 263 (58.45%) had poor disaster management knowledge and 9 (2%) had extremely good. On the post-test, 170 (38.22%) had strong disaster management knowledge and 33 (7.33%) had exceptional. Most 310 (69%) pre-test responders had a negative attitude about catastrophe management, while 140 (31%) had a positive attitude. After the test, 52% of 235 respondents had good attitude about catastrophe management and 48% negative attitude for it. At 0.05 significance level, demographic variables are associated with pre-test knowledge score. At a significance level of 0.05, the demographic variables are associated with pre-test attitude score. Conclusion: The education program enhances nursing students’ disaster management knowledge and attitudes, the study revealed. Nursing students’ knowledge and attitude rise.